A Tough Little Patch of History : Gone with the Wind and the Politics of Memory - Dickey, Jennifer W. (Book collections on Project MUSE., 2014)
Jennifer W. Dickey is assistant professor and coordinator, public history program, Kennesaw State University. She is the author of A History of the Berry Schools on the Mountain Campus and co-editor of Museums in a Global Context: National Identity, International Understanding.